PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPATU SPECS DI KALANGAN MAHASISWA ITB AHMAD DAHLAN JAKARTA - Yana Putra, Rizky Dwi; Budiasih, Yanti; Husnayetti, Husnayetti (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
With the advent of new technologies and the proliferation of online marketplaces, competition in the corporate sector has heated up in recent years. The sports shoe industry is one of the fastest-growing industries in Indonesia. The purpose of this study was to examine the relationship between Specs shoe purchases and variables including product quality, pricing, and brand image among students at ITB Ahmad Dahlan Jakarta. In this research, we used quantitative associative methods to examine the following variables: product quality (X1), price (X2), brand image (X3), and choice to buy (Y). One hundred participants were chosen for the research using a purposive sampling method, which entails selecting samples according to predetermined criteria. The data was collected via an online questionnaire. The technology used to analyse the data was Structural Equation Modelling (SEM) using SmartPLS 4.0. Product quality, pricing, and the choice to buy all have a positive correlation, according to this research. Additionally, it was shown that consumers' perceptions of brands had a substantial impact on their purchase choices. Product quality, pricing, and brand image are all examples of exogenous variables that, when combined, may influence consumers' final purchase choices.Keywords: brand image, price, purchase decision, product quality, specs shoes